The Nature and Activity of Liaison Psychiatry Services in Tertiary Care Hospital in Bangladesh: A Study in MMCH - Parvez, Muhammad Kabir Hasan; Podder, Bidhan Ranjon Roy; Ahmed, Kowser; Roy, Polash; Mian, Md Sazib; Sabuz, Dil Mohammad Sazzadul Kabir; Chowdhury, Taslima Yasmeen; Ghose, Tumpa Indrani; Khan, Enamul Hoque; Lashkar, Md Asaduzzaman; et al. (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Liaison Psychiatry is the study, practice and teaching of the association between medical and psychiatric ailments. Aim of the study: The aim of this study is to find out the referring department, reason for consultation, common psychiatric and medical comorbidities treatment pattern and sociodemographic of the referred patients to psychiatry department from the other departments of MMCH. Methods: This cross-sectional study was carried out from January 2011 to December 2020. Patients referred from different in-patient departments every day were taken as study population. Psychiatric diagnoses of the patients were assessed by the specialist psychiatrist as per DSM-5 standards. Results: Among the referred patients (n= 714) 56% were female; 60.4% were aged between 21-60 years; More than half of the patients were referred from different branches of Medicine (60.8%). ENT (14.8%), Gynae and Obstetrics (7.4%), surgery 3.6% and Neurology and pediatrics (3%) each. Other major sources of psychiatric referrals were cardiology (n=17, 1%), neurosurgery (n=6, 0.4%) and others (n=99, 6. The most prevalent DSM-5 diagnosis was bipolar disorder (22.1%) followed by Brief Psychotic Disorder (13%), Schizophrenia (8.6 %) Delirium 5.5% MDD 5.2% Panic Disorder 4.7%, GAD 0.4%, OCD 0.5%, SRD 0.6%, Dementia 1.8%, Conversion Disorder 3.6%, Post-partum Psychosis 4.6%, Adjustment Disorder 4.9% ,ID 0.3% and others 17.7 %. No psychiatric diagnosis was made in 5.5% of the referred patients. Pharmacological treatment given 87.7% patient, psychological treatment given to 8.8% patient, both treatments needed to 3.5% patient. 81.6% patient given treatment with advice, 15.5% transferred to department of psychiatry 2.9% referred to another department. Conclusion: Psychiatric comorbidities in overall medical diseases are very familiar. Liaison Psychiatry provides an opportunity to upgrade health outcomes for in-patients and reduce burdens on the healthcare system J Com Med Col Teachers’ Asso Jan 2025; 29(1):70-75